Riscos e crises: da teoria - Luciano Lourenço (Riscos e Catástrofes, 2018)
This book aims to frame the study of the different types of risk involving the intervention of civil protection agents, at the same time that it seeks to specify the meaning, in the Portuguese language, of some of the main concepts associated with risk theory and contributing to the definition of the methodology about the study of physical and human hazards, designed with a holistic character and therefore different from the parcelary analyses made by the science which contributes to the methodology of their respective specialties, whether it is natural sciences, social sciences and humanities or economic sciences. In this way and unlike these more specific sciences, which have a more specialised view and, therefore, also more in the risk, the sciences about the study of physical and human hazards seek to concentrate on the overall risk study, through a holistic view that encompasses the different types of manifestations because they materialize. In fact, only the sciences about the study of physical and human hazards possess all the risks as a central and unique object of study, involving all types and, also, their different phases of manifestation, from prevention to the recovery of areas where they have manifested themselves, and also their stakeholders, from the characters to the infrastructures, contrary to what happens to other sciences that consider the risks more as manifestations, which are studied only in aspects that relate to their specialty. Moreover, this approach about the study of physical and human hazards seeks to be global and systemic, that is, it tries to take into account all the elements that explain different types of risk, from its origin: natural, anthropic or mixed, to the consequences caused by its manifestation, both in people, in their goods and possessions. Finally, we consider that education is the most appropriate way to solve the problems resulting from the manifestation of risks, so that the technical-scientific knowledge, materialized in several knowledge, is fundamental for a properly sustained education. For all these reasons, the publication of this book aims to contribute to the knowledge about the study of physical and human hazards and, through it, to a better education and a greater resilience of the population to the manifestations of risk and, therefore, contribute to the reduction of the risk.